Japan's Postwar Party Politics - Kohno, Masaru (Princeton University Press, 1997)
In this sophisticated theoretical work, Masaru Kohno presents a systematic reexamination of the evolution of party politics in Japan since the end of the Second World War. Because of the long one-party dominance by the Liberal Democratic Party, Japan's parliamentary democracy has often been viewed as unique in the developed world, and most of the existing studies of Japanese party politics have addressed such determinants as its political culture, historical background, and socio-ideological cleavages. According to the author, these explanations do not adequately account for some of the most important changes that took place in Japanese party politics during the post-war period.